From the big bang to God : our awe-inspiring journey of evolution - Geering, Lloyd, 1918- (Salem, Oregon : Polebridge Press, 2013)
"A summary of the history of the universe through the lenses of science and the world's religions"--Publisher information.
Includes bibliographical references (p. 187-189) and index.
Description based on print version record.
Keywords: Evolution -- Religious aspects -- Christianity; Religion -- Philosophy; RELIGION / Comparative Religion; RELIGION / Essays; RELIGION / Reference; Electronic books